Mangiferina: microencapsulamento em sistemas pectina/quitosana, metabolismo intestinal in vitro e atividade anticancer - JosÃ Roberto Rodrigues de Souza (2012)
MANGIFERIN: MICROENCAPSULATION IN PECTIN/CHITOSAN SYSTEMS, IN VITRO INTESTINAL METABOLISM AND ANTICANCER ACTIVITY This work was performed in four parts: The first part refers to the isolation of pectin from a regional pumpkin in order to be used as matrix for drug encapsulation: Pumpkin (Cucurbita moschata) is an excellent and low cost source of carotenoids, precursors of vitamin A. Moreover, it is also a great source of natural and low-cost pectin. Pectin is a heterogeneous complex polysaccharide found in the primary cell wall of most cells and its effect on health is receiving growing interest for applications such as an ingredient in food products and in pharmaceutical formulations for drug encapsulation. In the first part of this work, high-methoxyl pectin was isolated from a regional pumpkin by the method of acid hydrolysis. The isolated pectin was characterized by FTIR, 1H and 13C NMR, GPC, elemental analysis and rheology. In the second part, pectin with chitosan samples were used for encapsulation procedure: Microencapsulation processes, such as spray-drying is an alternative to enhance solubility of bioactive materials and a good way to preserve, protect and control the release rate of a substance until it reaches its target in the body. Mangiferin is an active phytochemical present in various plants including Mangifera indica L. This substance is reported to have anti-cancer, antioxidant and other activities, but has a low solubility in aqueous medium. In the second part of this work we encapsulated mangiferin within four different natural polymers compositions by using spray-drying techniques. The products were characterized by FTIR, SEM and HPLC-ESI-MS. The efficiency of mangiferin incorporation into each encapsulate was calculated by HPLC. The highest encapsulation efficiency was determined to be for pectins using Polysorbate 80 (Tween 80) as emulsifier. In the third part of this work, a gut metabolic study with mangiferin was performed: Mangiferin has low bioavailability, already reported in many scientific publications, and is more available in the gut, where it will be metabolized into other compounds. The aim of the third part was to produce and identify mangiferin metabolites simulating intestinal conditions as well as their isolation and characterization using different techniques such as HPLC-ESI-MS, Semipreparative HPLC, Nano-ESI-MS, and 1H / 13C NMR. The fourth part refers to the investigation of the cytotoxicic effects of mangiferin and its metabolites in human cancer cell lines: The aim of the fourth study was to investigate the cytotoxic effects of mangiferin and its main metabolites in human cancer cell lines such as intestinal cancer cell line Caco-2 in order to observe the potential anticancer activity of these compounds in vitro.